2016
DOI: 10.1080/00016489.2016.1229025
|View full text |Cite
|
Sign up to set email alerts
|

Patients with severe-to-profound hearing impairment and simultaneous severe vision impairment: a quality-of-life study

Abstract: The patients with dual sensory loss were younger, were more likely to live alone, and had a lower level of education than the control group. The QoL of the study group was significantly negatively affected. In total, 89% of the study group had been rehabilitated with hearing aids, while 8% had received rehabilitation with cochlear implants. A total of 32% of the study group had received extended audiological rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
2
12
0
1
Order By: Relevance
“…The crude OR for PIRS suggested that compared to men, women with severe-to-profound hearing loss experienced a 1.2 times greater negative impact of hearing impairment on their daily life. In a recent study, Turunen-Taheri et al [33] found even greater negative effects with both crude and adjusted OR, with a 2.3 times greater negative impact on QoL (mean score 0.6) and 1.8 times greater negative impact on PIRS (mean score 62) for patients with severe vision impairments combined with severe-to-profound hearing loss, than the control group with severe-to-profound hearing impairment only.…”
Section: Eq5d and Pirsevaluation Of Health Status And Effect Of Hearimentioning
confidence: 91%
“…The crude OR for PIRS suggested that compared to men, women with severe-to-profound hearing loss experienced a 1.2 times greater negative impact of hearing impairment on their daily life. In a recent study, Turunen-Taheri et al [33] found even greater negative effects with both crude and adjusted OR, with a 2.3 times greater negative impact on QoL (mean score 0.6) and 1.8 times greater negative impact on PIRS (mean score 62) for patients with severe vision impairments combined with severe-to-profound hearing loss, than the control group with severe-to-profound hearing impairment only.…”
Section: Eq5d and Pirsevaluation Of Health Status And Effect Of Hearimentioning
confidence: 91%
“…Thirteen studies used measures of anxiety symptoms, two of which overlapped with the studies reporting diagnoses [16,18]. Four of the studies reporting symptoms used the Hospital Anxiety and Depression Scale-Anxiety (HADS-A); two with a cut-point for clinical significance of 8 or greater [25,26] and two with a cut-point of 10 or greater [27,28]. These cut-points are validated as indicative of mild and severe anxiety, respectively [29].…”
Section: Anxiety Measuresmentioning
confidence: 99%
“…No previously published study has focused on monitoring the CI procedure with the HADS instrument, as far as we know, and only a few studies on HI have used the HADS. 6,44 In conclusion, the level of anxiety and depression is low in this group both before and after CI. Compared with Carlsson et al, 6 the level of depression in this population is not as high, and does not correlate with the degree of HI, which might depend on methodological differences.…”
Section: Discussionmentioning
confidence: 60%